The Damage Control Surgery in Austere Environments Research Group (DCSAERG): A dynamic program to facilitate real-time telementoring/telediagnosis to address exsanguination in extreme and austere environments. Issue 1 (July 2017) - Kirkpatrick, Andrew W.; McKee, Jessica L.; McBeth, Paul B.; Ball, Chad G.; LaPorta, Anthony; Broderick, Timothy; Leslie, Tim; King, David; Wright Beatty, Heather E.; Keillor, Jocelyn; Tien, Homer
Abstract : ABSTRACT: Hemorrhage is the most preventable cause of posttraumatic death. Many cases are potentially anatomically salvageable, yet remain lethal without logistics or trained personnel to deliver diagnosis or resuscitative surgery in austere environments. Revolutions in technology for remote mentoring of ultrasound and surgery may enhance capabilities to utilize the skill sets of non-physicians. Thus, our research collaborative explored remote mentoring to empower non-physicians to address junctional and torso hemorrhage control in austere environments. Major studies involved using remote-telementored ultrasound (RTMUS) to identify torso and junctional exsanguination, remotely mentoring resuscitative surgery for torso hemorrhage control, understanding and mitigating physiological stress during such tasks, and the technical practicalities of conducting damage control surgery (DCS) in austere environments. Iterative projects involved randomized guiding of firefighters to identify torso (RCT) and junctional (pilot) hemorrhage using RTMUS, randomized remote mentoring of MedTechs conducting resuscitative surgery for torso exsanguination in an anatomically realistic surgical trainer ("Cut Suit") including physiological monitoring, and trained surgeons conducting a comparative randomized study for torso hemorrhage control in normal (1g) versus weightlessness (0g). This work demonstrated that firefighters could be remotely mentored to perform just-in-time torso RTMUS on a simulator. Both firefighters and mentors were confident in their abilities, the ultrasounds being 97% accurate. An ultrasound-naive firefighter in Memphis could also be remotely mentored from Hawaii to identify and subsequently tamponade an arterial junctional hemorrhage using RTMUS in a live tissue model. Thereafter, both mentored and unmentored MedTechs and trained surgeons completed resuscitative surgery for hemorrhage control on the Cut-Suit, demonstrating practicality for all involved. While remote mentoring did not decrease blood loss among MedTechs, it increased procedural confidence and decreased physiologic stress. Therefore, remote mentoring may increase the feasibility of non-physicians conducting a psychologically daunting task. Finally, DCS in weightlessness was feasible without fundamental differences from 1g. Overall, the collective evidence suggests that remote mentoring supports diagnosis, noninvasive therapy, and ultimately resuscitative surgery to potentially rescue those exsanguinating in austere environments and should be more rigorously studied.